The Effect of Corporate Governance Mechanisms on Audit Quality towards Earnings Quality of Jordanian Non-Financial Firms - Freihat F.A.Y.; Kadir M.R.A.; Kamarudin K.A.; Sapingi R. (Elite Scientific Publications, 2025)
This study investigates the effect of corporate governance mechanisms, audit quality and earnings quality with special emphasis on the mediating effects of audit quality in an establishing market environment. The study examines the impact of IB, BE, AC and family ownership on audit and earnings quality using a sample of non?financial listed firms in Amman stock exchange over the period from 2015 to 2021. In aggregate, CG mechanisms do not positively or negatively affect audit quality neither directly nor indirectly, according to the findings. On the other hand, institutional quality partially mediates the relationship between some of CG mechanisms especially audit committee activity and earnings quality, indicating that customer satisfaction constructs can enhance fraud prevention especially through enhancing enterprise image. These results are consistent with Agency and Stakeholder theories, that suggest that monitoring structures become more effective when coupled with rigorous external audit processes. Results from this study will provide practical signals for policymakers and regulators (especially firm-level regulator) in emerging markets, as it shows a need to reinforce audit quality, especially when the CG mechanisms are strong since it is necessary to improve avoidance logics on manipulation with earnings transparency and accountability. ? (2024), (Elite Scientific Publications). All rights reserved.